Searching with and against each other: Spatiotemporal coordination of visual search behavior in collaborative and competitive settings - Niehorster, Diederick C; Cornelissen, Tim; Holmqvist, Kenneth; Hooge, Ignace (Attention, perception & psychophysics, 2019)
Although in real life people frequently perform visual search together, in lab experiments this social dimension is typically left out. Here, we investigate individual, collaborative and competitive visual search with visualization of search partners' gaze. Participants were instructed to search a grid of Gabor patches while being eye tracked. For collaboration and competition, searchers were shown in real time at which element the paired searcher was looking. To promote collaboration or competition, points were rewarded or deducted for correct or incorrect answers. Early in collaboration trials, searchers rarely fixated the same elements. Reaction times of couples were roughly halved compared with individual search, although error rates did not increase. This indicates searchers formed an efficient collaboration strategy. Overlap, the proportion of dwells that landed on hexagons that the other searcher had already looked at, was lower than expected from simulated overlap of two searchers who are blind to the behavior of their partner. The proportion of overlapping dwells correlated positively with ratings of the quality of collaboration. During competition, overlap increased earlier in time, indicating that competitors divided space less efficiently. Analysis of the entropy of the dwell locations and scan paths revealed that in the competition condition, a less fixed looking pattern was exhibited than in the collaborate and individual search conditions. We conclude that participants can efficiently search together when provided only with information about their partner's gaze position by dividing up the search space. Competing search exhibited more random gaze patterns, potentially reflecting increased interaction between searchers in this condition.
Keywords: mužské pohlaví; Male; Collaboration; Humans; Female; Shared gaze; kompetitivní chování; Eye Movements; lidé; sociální chování; ženské pohlaví; odměna; Eye movements; reakční čas; Competition; Reward; Young Adult; Visual search; Social Behavior; mladý dospělý; dospělí; pohyby očí; Adult; Competitive Behavior; Reaction Time